ARTISTIC INTERPRETATION OF INDUSTRIAL DEVELOPMENT IN SIRDARYO REGION THROUGH THE LANDSCAPE GENRE OF FINE ARTS - Abdumajidova Ugiloy Ravshanjon kizi (Bright Mind Publishing, 2025)
This article analyzes the impact of industrial development in the Sirdaryo region on visual arts, particularly within the landscape genre. It examines the significance of the concept of industrial-natural landscapes formed by the integration of industrial facilities with the natural environment, highlighting its compositional, coloristic, and aesthetic dimensions. Additionally, the study briefly explores the artistic representation of labor and modernization, as well as the role of this theme in art education.
Keywords: Sirdaryo region, industrial landscape, natural landscape, visual arts, landscape genre, industrial-natural harmony, modernization, labor aesthetics, composition, colorism, ecological aesthetics, art education.